Cashew Apple: Nutritional Composition, Nutritive Value and Potentials as Commercial Feedstuff for Livestock - Ojediran, Taiwo K.; Olorunlowu, Segun Abraham; Oyekola, Oluwatosin; Olagoke, Olayemi C.; Emiola, Isiaka Adewale (Syiah Kuala University, 2024)
Cashew (Anacardium occidentale L.) apple is an underutilized false fruit that accompanies the cashew nut. This review critically examines the nutrient composition, nutritive value, and potential of cashew apple as commercial feedstuff for livestock. It encompasses a comprehensive analysis of the various constituents present in cashew apple, including macronutrients, vitamins, minerals, and phytochemical factors. By synthesizing information from a wide range of studies, this review highlights the considerable variations in the nutrient content of cashew apple and establishes various nutritive values for different livestock. Furthermore, this review suggests the need for further research to explore the full spectrum of health-promoting attributes and potential applications of cashew apple-derived components. Overall, this comprehensive assessment of the nutrient composition of cashew apple provides valuable insights for researchers, nutritionists, and food industry professionals seeking to unlock the nutritional potential of this often overlooked fruit.